Algorithmic Aspects of Cloud Computing First International Workshop, ALGOCLOUD 2015, Patras, Greece, September 14-15, 2015. Revised Selected Papers - Karydis, Ioannis; Sioutas, Spyros; Triantafillou, Peter; Tsoumakos, Dimitrios (Theoretical Computer Science and General Issues, 2016)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Workshop on Algorithmic Aspects of Cloud Computing, ALGOCLOUD 2015, held in Patras, Greece, in September 2015 in conjunction with ALGO 2015. The 13 revised full papers presented together with 2 tutorial papers were carefully reviewed and selected from 37 initial submissions. They cover a wide range of topics in two main tracks: algorithmic aspects of large-scale data stores, and software tools and distributed architectures for cloud-based data management.